2016
DOI: 10.1590/0102-33062015abb0331
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of seed dispersal in the Cerrado biome: ecological and phylogenetic considerations

Abstract: Th e investigation of the phylogeny of a group of organisms has the potential to identify ecological and evolutionary processes that have been occurring within a community. Seed dispersal is a key process in the life cycle of vegetation and refl ects diff erent reproductive strategies of plants to a set of ecological and evolutionary factors. Knowing the dispersal syndromes and fruits types of a plant community may help elucidate plant-animal interactions and colonization strategies of plants. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 75 publications
(88 reference statements)
4
48
2
5
Order By: Relevance
“…Analyses of the zoochorous syndromes in this study (ornithochory, mastochory, chiropterochory, myrmecochory and "mixed") found that they had low phylogenetic signal at the genus level, indicating that genetically closely related zoochorous fruits are likely to be very different morphologically. This contrasts with the recent findings of Kuhlmann & Ribeiro (2016), which showed that the main syndromes (zoochory, anemochory and autochory) had high phylogenetic signal in the Cerrado. It appears that the evolution of exclusively animal seed dispersal in tropical environments is phylogenetically flexible, such that plant-frugivore interactions can be very generalized, yet responding to a set of selective pressures of the environment, such as availability of dispersal agents (different groups of frugivores) and changes in vegetation structure (Fleming & Kress 2013).…”
Section: Phylogenetic Signal In Zoochorous Syndromescontrasting
confidence: 99%
See 3 more Smart Citations
“…Analyses of the zoochorous syndromes in this study (ornithochory, mastochory, chiropterochory, myrmecochory and "mixed") found that they had low phylogenetic signal at the genus level, indicating that genetically closely related zoochorous fruits are likely to be very different morphologically. This contrasts with the recent findings of Kuhlmann & Ribeiro (2016), which showed that the main syndromes (zoochory, anemochory and autochory) had high phylogenetic signal in the Cerrado. It appears that the evolution of exclusively animal seed dispersal in tropical environments is phylogenetically flexible, such that plant-frugivore interactions can be very generalized, yet responding to a set of selective pressures of the environment, such as availability of dispersal agents (different groups of frugivores) and changes in vegetation structure (Fleming & Kress 2013).…”
Section: Phylogenetic Signal In Zoochorous Syndromescontrasting
confidence: 99%
“…S2 in supplementary material) were found in the study area. These plant taxa represent almost 25% of the species, 65% of the genera and 91% of the families of zoochoric plants of the entire Cerrado biome (Kuhlmann & Ribeiro 2016). Fruit-eating birds and mammals represent almost half of the bird and mammal species of the Federal District (258/600), and also almost half of the bird and mammal species of the entire biome (540/1050).…”
Section: Proportions Of Fruits and Frugivoresmentioning
confidence: 99%
See 2 more Smart Citations
“…). (2) Occupancy would be lower in secondary savanna for species that have fruits as an important part of the diet (such as Azara's agouti Dasyprocta azarae , white‐lipped peccary Tayassu pecari , and lowland tapir Tapirus terrestris ), due to a decrease in zoochoric trees and shrubs (Kuhlmann & Ribeiro ) and because larger (thus, older) plants generally produce more seeds and fruits (Chapman et al . , Greene & Johnson , Zardo & Henriques ).…”
mentioning
confidence: 99%